Physical properties of plasmid Mor174, which determines bacteriocin production in Proteus morganii 174. - Williams, J A (1978)
Plasmid Mor174 has a molecular weight of 3.6 X 10(6) and a buoyant density of 1.6994 g/cm3. The covalently closed circular form has a sedimentation coefficient of 22S. These are 30 to 40 plasmid copies per genome equivalent, but growth in chloramphenicol results in amplification of the copy number to 600. In Proteus morganii 174, Mor174 coexists with a cryptic plasmid of molecular weight 15.8 X 10(6) and a buoyant density of 1.7170 g/cm3.